Mechanical Compression Behaviour of "Green" Rocket Propellants - Florin M. DÎRLOMAN; Traian ROTARIU; Adrian N. ROTARIU; Gabriela TOADER; Liviu C. MATACHE; Gabriel F. NOJA (Problemy Mechatroniki)
The issues related to mechanical resistance of solid rocket propellants, which can appear during storage or handling of the launching system, are considered to directly influence the burning performance. Thus, in this study, four new types of composite rocket propellants, based on an environmentally friendly oxidizer (phase-stabilized ammonium nitrate), a metallic fuel (aluminium), and a "green" polyurethane-based binder (synthesized from an oligomeric isocyanate and a blend of polyester-polyols obtained through the catalytic degradation of polyethylene terephthalate), were subjected to compression mechanical analysis in order to highlight the importance of the binder on the response given by the tested materials subjected to compressive loads. The samples showed remarkable mechanical performances, the experiments allowing us also to determine the influence of the binder composition and fuel granulation on mechanical properties of the composite propellant.